Physical exercise as a strategy to maintain autonomy in older adults (Research, Society and Development, 2025)
This narrative review examined evidence on the role of physical exercise in maintaining functional independence among older adults. Searches were conducted in PubMed, the Virtual Health Library (BVS), SciELO, and Google Scholar (2020–2025) using terms related to “older adults,” “exercise,” “functional capacity,” “activities of daily living,” and “quality of life.” We included randomized trials, observational studies, and systematic reviews/meta-analyses reporting functional outcomes (SPPB, TUG, gait speed, 6MWT, chair-stand, ADL/IADL) and health-related quality of life. Fourteen studies were synthesized narratively. Findings indicate that resistance training and multicomponent programs (strength, balance/coordination, aerobic component, and mobility) improve functional performance and quality of life. Combined physical-cognitive interventions outperform isolated modalities; chair-based protocols benefit frail profiles; aquatic therapy reduces pain and enhances function in knee osteoarthritis; and eHealth/tele-exercise interventions show efficacy for balance and functional capacity. Observational evidence supports the association between habitual activity and autonomy. Major limitations include heterogeneity in protocols and outcomes, small samples, and short follow-up periods. Overall, physical exercise—particularly multicomponent programs—emerges as an effective and adaptable strategy to preserve autonomy in older adults. Future research should standardize dosing and outcome measures and evaluate long-term clinical endpoints, including falls, hospitalizations, and sustained independence.